Understanding the Antecedents of the Routine Use of Mobile Health Services: A Person–Technology–Health Framework - Meng, Fanbo; Guo, Xitong; Peng, Zeyu; Zhang, Xiaofei; Lai, Kee-hung (Frontiers in Psychology, 2022)
Although numerous studies have been conducted to understand the antecedents of usage of mobile health (mHealth) services, most of them solely focus on characteristics of mHealth services themselves but neglect taking users’ psychological and health-related factors into consideration. Besides, a comprehensive understanding of what influences users’ routine use intentions regarding mHealth services is lacking. Therefore, this study proposes a person-technology-health framework that underlines how personal factors (e.g., personal innovativeness in IT), technological factors (e.g., trust), and health factors (e.g., perceived health severity) jointly influence individuals’ routine use intentions regarding mHealth services. The proposed research model and related hypotheses were tested based on survey data from 270 respondents. The results indicate that personal innovativeness in IT, trust, and perceived health severity are important for enhancing routine use intention of mHealth services. Specifically, in situations of high perceived health severity, trust relates less positively to routine use intention than personal innovativeness in IT. In contrast, in situations of low perceived health severity, trust relates more positively to routine use intention than personal innovativeness in IT. The research findings extend the existing literature on routine use intention related to mHealth services and provide significant implications for practitioners.